2022
DOI: 10.1101/2022.02.22.481460
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Complete sequence of a 641-kb insertion of mitochondrial DNA in the Arabidopsis thaliana nuclear genome

Abstract: Intracellular transfers of mitochondrial DNA continue to shape nuclear genomes. Chromosome 2 of the model plant Arabidopsis thaliana contains one of the largest known nuclear insertions of mitochondrial DNA (numts). Estimated at over 600 kb in size, this numt is larger than the entire Arabidopsis mitochondrial genome. The primary Arabidopsis nuclear reference genome contains less than half of the numt because of its structural complexity and repetitiveness. Recent datasets generated with improved long-read seq… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…First, it was important to determine whether the msh1 mutant background altered the relative numbers of organellar genome copies. Second, numts (i.e., copies of mitochondrial DNA inserted into the nuclear genome) are known to be present in the Arabidopsis thaliana nuclear genome ( 102 104 ), and we wanted to correct for this in our heteroplasmy analysis.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…First, it was important to determine whether the msh1 mutant background altered the relative numbers of organellar genome copies. Second, numts (i.e., copies of mitochondrial DNA inserted into the nuclear genome) are known to be present in the Arabidopsis thaliana nuclear genome ( 102 104 ), and we wanted to correct for this in our heteroplasmy analysis.…”
Section: Methodsmentioning
confidence: 99%
“…For mitochondria, both primer sets amplify numts, so the values were adjusted based on the number of numt copies. The amplified regions of cox2 and rps12 are present at one and three numt copies, respectively, in the Arabidopsis nuclear genome ( 104 ). These values were subtracted from the calculated values of mitochondrial copies per genome before averaging to obtain a final value.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…First, it was important to determine whether the msh1 mutant background altered the relative numbers of organellar genome copies. Secondly, numts (nuclear mitochondrial DNA, i.e., copies of mitochondrial DNA inserted into the nuclear genome) are known to be present in the A. thaliana nuclear genome [96][97][98] and we wanted to correct for this in our heteroplasmy analysis.…”
Section: Organellar Genome Copy Numbermentioning
confidence: 99%
“…Considering the importance of epigenetic modifications in gene activity (Feng and Jacobsen 2011; Zhang, et al 2018) , the role of epigenetic silencing in the transcriptional inactivation of NUPGs/NUMGs should be explored. Three exemplary studies on the inactivation of NUPGs/NUMGs independently reported NUPTs/NUMTs as the alien nuclear genetic materials (like TEs) to be silenced through genomic defense (Zhang, et al 2020) , the important role of DNA methylation against NUPTs to maintain genome stability (Yoshida, et al 2019) , and the possible role of epigenetic modification in the silencing of a NUMT fragment in Arabidopsis (Fields, et al 2022) . However, these studies did not compare the DNA methylation patterns of NUPGs/NUMGs with the indigenous nuclear genes; moreover, the generality of their conclusions remained unclear.…”
Section: Introductionmentioning
confidence: 99%